Reimagining quality education for pastoralists through Maasai elders’ eyes in Monduli, Tanzania - Joseph C. Pesambili (Quality Education for All)
Purpose – While extensive research exists on education practices among Maasai pastoralists, this study fills a gap in understanding their specific perspectives on what constitutes “quality education” for their community. This study aims to uncover how Maasai elders define quality education based on the capabilities and functionings they value. Design/methodology/approach – The study used a glocalised research design informed by Sen’s capabilities approach to guide data collection, analysis and interpretation. Data were primarily gathered through in-depth interviews with two local chiefs, two firestick patrons and eight male and ten female elders in Monduli. Findings – The results illuminate the Maasai’s endorsement of education for self-improvement, cultural preservation, self-reliance and community service as essential components of quality education. These findings highlight the need for integrating these education-related capabilities into school curricula to enhance the Maasai community’s well-being and empowerment. The study also underscores the pivotal role of enkigúɛ́na as a Maa concept for facilitating constructive dialogue between Indigenous and Western knowledge, enabling meaningful engagement between the Maasai and educational stakeholders, and fostering internal discussions on the essence of quality education. The study concludes with implications for theory, policy, practice and further research. Originality/value – This paper offers a unique exploration of Maasai elders’ views on what constitutes “quality education” within their society. It also examines how the Maa term enkigúɛ́na (meeting) can act as an effective conduit for realising such educational aspirations.